A study of learning management system with E-learning - Alfarsi G.; Sulaiman H.; Tawafak R.M.; Malik S.; Jabbar J.; Alsidiri A. (Science and Engineering Research Support Society, 2023)
E-Learning field growing dramatically in this generation. Today generation is the technology time that uses technology universally. It is making learning easier and flexibility in taking materials. The management of the learning system is the core issue to develop the skills of learning and improving the students performance of learning. The students face problems in learning using the traditional methods and regular activities and that reveals to their level of the study. We conduct a survey on the e-learning system and discuss the method used. The finding was recommended for some e-learning system than the other based on the result of students' skills. This reveals of using the e-learning system reflected its result in educational instructional significantly in the high level of the study of the students and student's performance. ? 2019 SERSC.